Characteristics Of The Dominant Plant Morphology In The Watershed Of Batang Arau Padang City Of West Sumatra - Vino Restu dwi putri; Vauzia Vauzia (Universitas Negeri Padang, 2021)
Riparian vegetation is vegetation that grows around river flows and has an important role in river ecosystems. The area of Sungai Arran (DAS) Batang Aru is one of the river areas that have been used for factories and fields, so there is concern that it will have an impact on riparian vegetation along the watershed. Plants will show a response to environmental changes. Leaves are an organ that is sensitive to environmental changes. This research was conducted from December 2020-February 2021. The research was carried out in 3 locations along the Arau watershed, namely: the factory area, the field area, and the natural area. This research is descriptive research. Morphological character data were analyzed using the T test at a significant level of 5%. The results showed that the dominant plant species was Homalanthus populneus. Leaf morphological characters of H. populneus in the factory area vs the field area did not show significant differences in leaf length, leaf width, leaf stalk length but did show significant differences in the number of leaf branches. The plant area VS the unspoiled area showed significant differences in leaf length, leaf width, leaf stalk length and number of leaf branches. Field area VS unspoiled area showed significant differences in leaf length, leaf width, leaf stalk length, while the number of leaf branches showed no significant difference.